Decentering international relations - Nayak, Meghana (Zed Books ; Distributed in the USA by Palgrave Macmillan, 2010)
Decentering International Relations seeks to actively confront, resist, and rewrite IR, a discipline which is deeply centered in the North/West and which privileges certain perspectives, pedagogies, and practices. Through engagement with a variety of theories and in conversation with scholars, activists, and students, Meghana Nayak and Eric Selbin invite the reader to participate in an accessible yet provocative experiment to decenter the North/West when we learn, study, and do IR. Decentering International Relations is a remarkable and provocative re-envisioning of a globally important subjec.